Penentuan Faktor Dominan Kerusakan Camshaft pada Diesel Generator Kapal MT. Sapta Samudra melalui Analisis SHEL dan USG - Afdolludin Afta Tazani; Marihot Simanjuntak; Retno Sawitri; Susi Herawati (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
In the context of maintenance and overhaul carried out when a machine has reached the running hour limit, it is necessary to prepare spare parts according to the manual book instructions to replace the engine parts that must be replaced in order to support the smooth running of the overhaul so that no damage occurs after the diesel engine generator is overhauled, especially the camshaft whose working system continues to receive needs and pressure while the machine is operating, so maintenance must be more for the sake of the diesel engine generator, if there is negligence or replacing spare parts not according to the manual book when doing an overhaul, the consequences that arise are such as erosion of the camshaft. In this case, the researcher used the SHEL method to map the problem and used the USG method for discussion. Data collection techniques in the form of an approach to objects through observation, interviews and literature studies. The purpose of this study was to determine what factors cause erosion of the diesel engine generator camshaft, what impacts are caused by the erosion of the diesel engine generator camshaft and what efforts are made to overcome the erosion of the diesel engine generator camshaft.